PENGARUH KEPEMIMPINAN MANAJERIAL KEPALA SEKOLAH, SUPERVISI PENGAWAS, KOMITMEN BERPRESTASI, DAN KOMPETENSI GURU TERHADAP KINERJA GURU SMA NEGERI DI KOTA SAMARINDA - suriansyah; Dwi Nugroho; Usfandi Haryaka (BEduManagers Journal : Borneo Educational Management and Research Journal, 2020)
The objective of this research is to obtain information concerning the effect of headmaster managerial leadership, supervisory supervision, achievement commitment, teacher competence, toward teacher, performance. The research was conducted in Samarinda City. Survey method apllied in this research which data have been analyzed by path analisis. In this research, teachers have been choosen as unit analysis and 154 samples selected randomly. This research findings are as follows: (1) The managerial leadership of the principal directly affects teacher performance, (2) Supervision of supervisors does not directly affect the performance of teachers, (3) Commitment to achievement directly affect the performance of teachers, (4) Teacher competence has a direct effect on teacher performance, (5) Managerial leadership of the principal has a direct positive effect on teacher competence, (6) Supervision of supervisors does not directly affect the competence of teachers, (7) Commitment to achievement has no direct effect on teacher competence, (8) The managerial leadership of the principal directly influences the achievement commitment, and (9) Supervision of supervisors has no direct effect on achievement commitments.Therefore, the performance of teachers of SMA Negeri in Samarinda City can be improved through headmaster's managerial leadership, achievement commitment and teacher competence, teacher competence can be improved through headmaster's managerial leadership, and achievement commitment can be improved through headmaster's managerial leadership